Odpowiedź :
a) a - (a -1 + a) = a - a + 1 - a = 1 - a
b) -x -(-1 + x - x + 1) = -x - 0 = -x
c) x - (y - x + y - x - y + x) = x - y + x = 2x - y
b) -x -(-1 + x - x + 1) = -x - 0 = -x
c) x - (y - x + y - x - y + x) = x - y + x = 2x - y
1. a-[a-(1-a)]=a-[a-1+a]=a-a+1-a=1-a
2. -x-[-(1-x)-(x-1)]=-x-[-1+x-x+1]=-x
3. x-[y-(x-y)-x-(y-x)]=x-[y-x+y-x-y+x]=x-[-x+y]=x+x-y=2x-y
2. -x-[-(1-x)-(x-1)]=-x-[-1+x-x+1]=-x
3. x-[y-(x-y)-x-(y-x)]=x-[y-x+y-x-y+x]=x-[-x+y]=x+x-y=2x-y
1)a-[a-(1-a)]=a-[a-1-a]=a-a-1-a=-3a-1
2) -x-[-1+x-x+1]=-x+1-x+x-1=-x
3) x-[y-(z-y)-x-(y-x)]=x-y-x+x-y+x+y-x=2x-y
2) -x-[-1+x-x+1]=-x+1-x+x-1=-x
3) x-[y-(z-y)-x-(y-x)]=x-y-x+x-y+x+y-x=2x-y